Dynamic thiol/disulfide homeostasis in patients with lichen planus. Issue 1 (3rd August 2018) - Kalkan, Göknur; Emre, Selma; Alisik, Murat; Aktaş, Akın; Baran, Pervin
Abstract : Objective: Lichen planus (LP) is an autoimmune inflammatory disease of the mucocutaneous tissue, whose exact pathological course remains unclear. Abnormal thiol/disulfide homeostasis has been postulated to be responsible for a number of diseases predominated by chronic inflammation. To be able to contribute complicated and unclear pathogenesis of LP, we aimed to investigate dynamic thiol/disulfide homeostasis in patients with LP, using an original automated method developed by Erel and Neselioglu in this study. Methods: The study group consisted of 81 unrelated patients with LP and 80 unrelated healthy controls with no LP lesions in their personal history or on clinical examination. Thiol/disulphide homeostasis tests have been measured with a novel automatic spectrophotometric method developed and the results have been compared statistically. Results: Native thiol and total thiol levels were found as significantly higher in patients with LP than the control group ( P = 0.026 and 0.035, respectively). There was no significant difference between the disulfide levels of the patients with LP and the control group. Conclusions: We provide evidence that that thiol/disulphide homeostasis impaired in favor of thiol levels in LP patients compared to the control group based on the data of our study. To the best of our knowledge, the present study is the first examination on the correlation between thiol and disulfide homeostasis in patients with LP.